Effect of Binary Organic Solvent Mixtures on Lipase-Catalyzed Regioselective Acylation of 6-Azauridine with Various Structural Vinyl Esters - Bi1, Yanhong; Du1, Wenying; Wang1, Zhaoyu; Nie1, Linghong; Zhao1, Xirong (Asian Journal of Chemistry, 2014)
In this paper, the regioselective acylation of 6-azauridine for preparing its potential prodrugs was successfully conducted in the hydrophobicity-based binary solvent system using Candida antarctica lipase B. Comparative study showed that the reaction rate, thermal and operational stability of the enzyme were dramatically improved by using the binary mixtures of acetone and isooctane (85:15, v/v) as the reaction medium. In addition, the acyl donor sturcture displayed great influence on the behaviour of the enzyme in binary solvent system, presumably due to their different interactions with the active site of the lipase.